Population Structure (Mangifera Casturi Koestrm) In The Lake Sari Embun Area, Tanah Laut District - Sofhia, Nida; Dharmono, Dharmono; Irianti, Riya (Biospecies, 2024)
Population structure is used to determine the condition and existence of populations in a habitat. Kasturi is one of the plants found in the Danau Sari Embun area, Tanah Laut Regency. This research aims to describe the structure of the Kasturi population in the Danau Sari Embun Area, Tanah Laut Regency. The research results show that the structure of the Kasturi population in the Danau Sari Embun area has the shape of a pyramid of pots or disturbed jugs with two growth phases, namely the reproductive phase and the post-reproductive phase. Kasturi plants found in the Danau Sari Embun area are categorized as critical, namely 0.44 Ind/Km².